The Current Impact of Incidental Findings Found during Neuroimaging on Neurologists’ Workloads - Booth, Thomas C.; Boyd-Ellison, Jennifer M. (PLOS ONE, 2015)
Objective Neuroimaging is an important diagnostic tool in the assessment of neurological disease, but often unmasks Incidental Findings (IFs). The negative impacts of IFs, such as ‘patient’ anxiety, present neurologists with management dilemmas, largely due to the limited knowledge base surrounding the medical significance of these IFs. In particular, the lack of evidence-based clinical trials investigating the efficacy of treatments for subclinical IFs makes management protocols challenging. The objective was to determine the impact IFs may have on neurologists’ workloads and healthcare budgets and to examine neurologists’ concerns regarding the clinical management of these ‘patients’. Methods Qualitative research based on constructivist grounded theory. Data was collected through semi-structured interviews of purposively sampled neurologists, coded, and concurrent comparative analysis performed. A substantive theory of the ‘IF impacts’ was developed after concept saturation. Results Neurologists managed the escalating workload caused by an increased number of referrals of ‘patients’ with IFs found during neuroimaging; however it was unclear whether this was sustainable in the future. Neurologists experienced IF management dilemmas and spent more time with ‘patients’ affected by anxiety. The lack of information provided to those undergoing neuroimaging by the referring clinician regarding the possibility of discovering IFs was highlighted. Conclusion The impact of IFs upon the neurologist, ‘patient’ and the health institution appeared considerable. Further research determining the natural history of subclinical IFs and the efficacy of intervention will help to alleviate these issues.